1967
DOI: 10.1111/j.1151-2916.1967.tb15102.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria in the System GeO2‐Al2O3

Abstract: The low-temperature a-modification is formed by a distortion of the hexagonal @-NbC. The distorted modification may be thought of as being formed by compressing the hexagonal parent cell perpendicular to one of the principal prism planes, thus effecting an approximately equal (but opposite in sign) length change of the base plane vectors. This behavior is immediately reflected by comparing the hexagonal pseudoaxes of alH = 3.092 A and = 3.145 A in the orthorhombic structure with the base length of U H = 3.118 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 4 publications
2
2
0
Order By: Relevance
“…It is found that, from this value, the composition ratio of the Al oxide and the Ge 3+ component is 3 to 1. This ratio corresponds well to the ratio of a stable AlGeO phase, which is Al 6 Ge 2 O 13 (16). In addition, we also found that the crystallized AlGeO layer was formed at the Al 2 O 3 /Ge interface with PTO at 550°C for 30 s through observations of cross-sectional transmission electron microscopy and transmission electron diffraction (TED) (11).…”
Section: Resultssupporting
confidence: 73%
“…It is found that, from this value, the composition ratio of the Al oxide and the Ge 3+ component is 3 to 1. This ratio corresponds well to the ratio of a stable AlGeO phase, which is Al 6 Ge 2 O 13 (16). In addition, we also found that the crystallized AlGeO layer was formed at the Al 2 O 3 /Ge interface with PTO at 550°C for 30 s through observations of cross-sectional transmission electron microscopy and transmission electron diffraction (TED) (11).…”
Section: Resultssupporting
confidence: 73%
“…As was reported in [42] the mullite-like phases, such as the germanium-mullite types Al2GeO5, Al2,26Ge0,74O4,87, Al2,38Ge0,62O4,81, and Al2,4Ge0,6O4,8, tended to crystallize rapidly. These crystalline phases were dispersed in the amorphous phases of glass.…”
Section: Discussionsupporting
confidence: 78%
“…Schneider and Werner 7 studied the high temperature reactions of GeO 2 , Al 2 O 3 and Ga 2 O 3 , ®nding that andalusite-type germanates were favored at lower temperatures and Al contents, while higher temperatures and Al contents favored 3 : 2 mullite-type germanates. Phase equilibrium studies in the GeO 2 ±Al 2 O 3 system predict only germanium±mullite (3Al 2 O 3 ?2GeO 2 or Al 6 Ge 2 O 13 ), 8 but two other Al±Ge±O phases are also known. These are Al 2 GeO 5 , which has the kyanite structure 9 and the digermanate Al 2 Ge 2 O 7 , which, unlike thortveitite (Sc 2 Ge 2 O 7 ), 10 contains AlO 5 bipyramids.…”
Section: Introductionmentioning
confidence: 99%